Microfilaremic infection in canine filariosis in Colombia: a challenge in morphological and molecular diagnostics - Esteban-Mendoza, María Victoria; Arcila-Quiceno, Victor Hernán; Ríos Chacón, Catalina; Jaimes Dueñez, Jeiczon Elim; Tique Oviedo, Marisol; Díaz Bustos, Alejandro; Castellanos, María Fernanda; Morchón, Rodrigo (Frontiers in Veterinary Science, 2024)
Canine filariosis is caused by filiform nematodes and affects several species of animals as well as humans. The disease produces a wide range of symptoms that can often be confused with other diseases, which increases the complexity of its diagnosis. The search for methodologies to facilitate its diagnosis is a challenge, and specific and differential identification of the parasite species causing the disease holds key to a successful diagnosis. In Colombia, there is a problem of underdiagnosis of filariosis in microfilaremic dogs infected by Dirofilaria immitis and Acanthocheilonema reconditum, and of microfilaremias not related to heartworm disease. The highest prevalences have been reported for D. immitis infections, although new cases of A. reconditum infections are beginning to appear. The aim of this study was to differentiate the microfilariae infections caused by D. immitis and A. reconditum by a morphological and molecular characterization of microfilariae so as to facilitate an accurate diagnosis of canine filariosis in the metropolitan area of Bucaramanga (Colombia). For this purpose, 400 blood samples with anticoagulants were collected from the dogs and analyzed with the help of a commercial immunochromatography kit for the detection of D. immitis circulating antigen. The Woo, Knott, and polymerase chain reaction (PCR) techniques were employed for determining the parasite count, morphological observation, and molecular identification of microfilariae present in the dogs respectively. The prevalence of microfilaremic dogs in Bucaramanga metropolitan area was 18.75% (75/400). The prevalence of dogs that tested positive for D. immitis in the antigen and in PCR tests was 1.25% (5/400) and 1% (4/400), respectively. Furthermore, the PCR test revealed that 17.75% of the microfilaremic dogs tested positive for A. reconditum (71/400) (first report in the metropolitan area of Bucaramanga), with one animal co-infected by both species, and 0% for D. repens (0/400). However, by morphological characterization, 4% of the microfilariae (3/75) corresponded to D. immitis, 20% (15/75) to D. repens, and 76% (57/75) to A. reconditum. The use of molecular diagnostic methods such as PCR aids in the specific identification of the parasite, thus making it a more accurate method than the morphological characterization of microfilariae. The identification of the parasites by PCR helps improve the veterinary diagnosis of canine filariosis in Colombia, which would lead to the establishment of an appropriate treatment protocol for each species of filaria and also to the generation of reliable data to be used at the clinical and epidemiological levels.